The Chilean infant mortality decline: improvement for whom? Socioeconomic and geographic inequalities in infant mortality, 1990-2005 - Alexander Warren Hertel-Fernandez; Alejandro Esteban Giusti; Juan Manuel Sotelo
OBJECTIVE: To measure socioeconomic inequalities and differential risk in infant mortality on national and regional levels in Chile from 1990 to 2005, and propose new policy targets. METHODS: The study analysed Chilean vital events registries from 1990 to 2005 for infant mortality by maternal education, head of household occupational status, cause, age and location of death. Annual infant mortality rates and relative risk were calculated by maternal education and head of household occupational status for each cause and age of death. Socioeconomic inequalities were then mapped to 29 regional health services. FINDINGS: Reductions in the national infant mortality rate were driven by reductions among highly educated mothers, while recent stagnation in the national rate is caused by high levels of infant mortality among uneducated mothers. These vulnerable households are particularly prone to infant mortality risk due to infectious disease and trauma. We also identify clustering of high socioeconomic inequalities in infant mortality throughout the poorer north, indigenous south and densely populated metropolitan centre of Santiago. Finally, we report large inequities in vital statistics coverage, with infant deaths among vulnerable households much more likely to be inadequately defined than in the remaining population. CONCLUSION: These results indicate that the socioeconomically disadvantaged in Chile are at a significantly higher risk for infant mortality by infectious diseases and trauma during the first month of life. Efforts to reduce national infant mortality in Chile and other countries must involve policies that target child survival for at-risk populations for specific diseases, ages and locations.